FORMATION OF PROFESSIONAL DIRECTION OF FUTURE DEFECTOLOGISTS - Mirbobayeva Nodirakhan Soliyevna (Galaxy International Interdisciplinary Research Journal, 2023)
This article reveals the main features of the process of forming the professional direction of future defectologists in the higher education system. The characteristics of the contingent of modern defectologist students conditioned by objective socio-economic and cultural conditions, which have a positive and negative effect on the formation of their professional direction, are studied. The possibilities of the modern higher education system are shown, which allows it to be effectively formed among future defectologists.